The comparison of analytical methods used to measure bone mineralization across different bones, ages of pig, dietary differences, and health statuses - Williams, Hadley Reginald (Kansas State University, 2023)
Chapter 1 utilized a total of 2,184 pigs in a 143-d study to evaluate the effects of feeding varying analyzed calcium to phosphorus ratios (Ca:P) at two standardized total tract digestible (STTD) phosphorus to net energy ratios (STTD P:NE). The results suggested that pigs fed High STTD P:NE had improved overall ADG, G:F, and bone mineralization compared to pigs fed diets at 75% of High levels. Additionally, increasing the analyzed Ca:P ratio worsened ADG, G:F, and bone mineralization with Low STTD P:NE but had marginal impacts when adequate STTD P:NE was fed. Chapter 2 utilized a total of 360 nursery pigs in a 28-d trial to evaluate the effects of different bones and analytical methods on the assessment of bone mineralization response to dietary P and vitamin D in nursery pigs. The results suggested that bone density and bone ash responses varied depending on bone analyzed. Differences in bone density and ash in response to P and vitamin D were most apparent with fibulas and 2nd ribs. There were apparent differences in the bone ash percentage between defatted and non-defatted bone. However, differences between the treatments remain consistent regardless of the analytical procedure. For histopathology, 10th ribs were more sensitive than 2nd ribs or fibulas for detection of lesions. Chapter 3 utilized a total of 882 finishing pigs in a 112-d study to evaluate the effects of different bones and analytical methods on the assessment of bone mineralization response to changes in dietary P, phytase, and vitamin D in growing pigs. The results suggested there are differences between bone ash procedures was more apparent than the differences between diets. Differences in bone density and mineral content in response to dietary P and vitamin D were most apparent with 10th ribs. Also, healthy pigs had greater serum Ca, P, and vitamin D concentrations and defatted bone ash than those exhibiting clinical signs of illness, with no difference between the two health statuses when expressed on a non-defatted bone ash basis. Chapter 4 utilized 194 pigs from 64 commercial sites across 14 production systems in the Midwest US were used in a diagnostic survey to evaluate baseline biological measurements used to determine bone mineralization. In the diagnostic survey, there were differences in serum Ca, P, and vitamin D between healthy, lame, and unhealthy pigs. Differences in bone mineralization between pig types varied depending on the analytical procedure and bone and there was considerable range in values within pig type across the 14 production systems sampled. Chapter 5 utilized 4,887 bones from 8 different experiments to compare different bones and analytical procedures used to measure bone mineralization. The study highlights that bone density and bone ash can be used to determine bone mineralization in nursery and finishing pigs, with defatted preferred in finishing pigs due to reducing the variation. The study also suggests that the procedures for bone density are simpler and allow for a more rapid assessment of bone mineralization compared to bone ash with a reasonable degree of correlation.
Keywords: Swine; Calcium; Phosphorus; Bone mineralization; Vitamin D; Growing pigs